Chest ultrasound findings in pulmonary tuberculosis. (October 2017) - Agostinis, Paolo; Copetti, Roberto; Lapini, Laura; Badona Monteiro, Geraldo; N'Deque, Augusto; Baritussio, Aldo
In resource-limited countries, the diagnosis of pulmonary tuberculosis (TB) is based on clinical findings, chest radiography and the demonstration of acid-fast bacilli in sputum. Few data are available on the use of ultrasound (US) to diagnose pulmonary TB. Chest US was performed in patients with lung TB from a rural African setting, to look for signs of the disease and to clarify the role US may have in the diagnosis of pulmonary TB. Sixty adult patients diagnosed with lung TB underwent chest US. All patients had abnormal findings. The most frequent was a subpleural nodule (SUN), which was mostly multiple and also found in radiologically normal areas. Other findings were lung consolidations, cavitations, miliary patterns made of miniature SUNs, and pleural and pericardial effusions. Chest US is a complementary tool in evaluating patients with suspected lung TB in resource-limited settings where the disease has high prevalence.